America Overcommitted : United States National Interests in the 1980s - Nuechterlein, Donald E., 1925- (Book collections on Project MUSE., 1985)
Is the United States seriously overcommitted in its worldwide relationships? This book provides the answers to that question. It will be essential reading for makers of American foreign and national security policy, for journalists reporting on international affairs, for scholars seeking better ways to analyze United States foreign policy objectives, and for informed citizens who ask why the United States is involved militarily in all parts of the world.